Pola Komunikasi Sekunder Group Discord Heroes E-Sports Studi Pada Remaja Di Kelurahan Pahlawan - Syaidhina Rizki (CV. ITTC INDONESIA, 2023)
Secondary communication is communication that is carried out using media or tools as a means to be able to communicate with anyone and anywhere or not limited by space and time and the amount. If the communicant is far from reach, a telephone or letter is used, as well as many communicants, loudspeakers are used, if there are far and many, then newspapers, radio or television and other broadcast media are used. There is a media or application called Discord which is commonly used by the average community, especially the Heroes E-Sports group, to communicate via devices such as cellphones and even laptops/PCs. This research was conducted aiming to see how the process or form of secondary communication that occurs when a community or group is carrying out their respective activities. By using a descriptive qualitative research method through various data collection techniques, namely observation, interviews, and documentation. The results showed that the pattern of secondary communication in the Discord Heroes E-Sports group occurred according to the pattern and the communication that took place was very good and responsive. In addition, this research also shows that communication via social media, especially the Discord application, is in great demand, with this Discord can very well become a mobile application for all users to communicate. In conclusion, secondary communication can occur anywhere and anytime using any application that they normally use on a daily basis to support unlimited communication activities. Therefore, it is also necessary to make efforts to improve the quality of the connection or signal and even devices that are used by many people, so that communicating via social media becomes more optimal and reduces interference.